2015
DOI: 10.1186/s13578-015-0053-7
|View full text |Cite
|
Sign up to set email alerts
|

Ouabain prevents pathological cardiac hypertrophy and heart failure through activation of phosphoinositide 3-kinase α in mouse

Abstract: Background Use of low doses of digitalis to prevent the development of heart failure was advocated decades ago, but conflicting results of early animal studies dissuaded further research on this issue. Recent discoveries of digitalis effects on cell signal pathways prompted us to reexamine the possibility of this prophylactic action of digitalis. The specific aim of the present study was to determine if subinotropic doses of ouabain would prevent pressure overload-induced cardiac remodeling in the mouse by act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 37 publications
3
33
0
Order By: Relevance
“…In our study, higher FOXO3 and Beclin expressions were observed in rabbits with HF compared with those in the control group, and CCM signals application significantly decreased their expressions (Figure 3). Wu et al [26] reported that the activation of Pi3k expressions in the mouse heart could prevent cardiac remodeling. In this study, lower Pi3k expressions were observed in the HF group than in the control group, and their concentrations significantly increased in the CCM and (e) western blot images of mTOR, p-mTOR, GSK-3β, and TORC2.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, higher FOXO3 and Beclin expressions were observed in rabbits with HF compared with those in the control group, and CCM signals application significantly decreased their expressions (Figure 3). Wu et al [26] reported that the activation of Pi3k expressions in the mouse heart could prevent cardiac remodeling. In this study, lower Pi3k expressions were observed in the HF group than in the control group, and their concentrations significantly increased in the CCM and (e) western blot images of mTOR, p-mTOR, GSK-3β, and TORC2.…”
Section: Discussionmentioning
confidence: 99%
“…; Wu et al. ). The most documented example of protection against ischemia‐reperfusion injury by a CG is ouabain preconditioning (OPC).…”
Section: Introductionmentioning
confidence: 98%
“…Ouabain binding to the a-subunit of Na + /K + -ATPase also initiates specific intracellular signaling pathways, most notably PI3K/Akt and c-Src/ERK in the cardiac tissue of various species (Mohammadi et al 2001(Mohammadi et al , 2003Liu et al 2007; Morgan et al 2010;Bai et al 2013;Duan et al 2015). Based on experimental evidence reported in recent years, the concept that these intracellular events occur at low (subinotropic) concentration and lead to additional cardiac actions of CG such as hypertrophic growth, prevention of cardiac hypertrophy and failure, and protection against ischemia-reperfusion injury has emerged (Liu et al 2007;Pasdois et al 2007;Pierre et al 2007;D'Urso et al 2008;Morgan et al 2010;Bai et al 2013;Belliard et al 2013;Duan et al 2015;Wu et al 2015). The most documented example of protection against ischemia-reperfusion injury by a CG is ouabain preconditioning (OPC).…”
Section: Introductionmentioning
confidence: 99%
“…In rat and rabbit hearts short exposure to a low concentration of ouabain protects the heart against ischemia/reperfusion injury. Current reports confirm cardio protection induced by ouabain [9]. It is suggested that ouabain can be beneficial to various stages of heart failure [10].…”
mentioning
confidence: 75%